Calculation of the Choroidal Vascularity Index and Tissue Distribution Indexes in Different Retinal and Choroidal Regions by Employing Digital Image Processing Techniques in Optical Coherence Tomography Images - Abdullah Soylu; Güner Üney; Deniz Somer; Onur İnam (Genel Tıp Dergisi)
Objective: In this study, it is aimed to investigate the optical coherence tomography images of healthy subjects for various parameters and tissue distribution indexes. Materials and Methods: 100 eyes of 50 healthy case’s optical coherence tomography (OCT) images have been employed for analysis. Total retinal area (TRA), dark retinal area (DRA), light retinal area (LRA), dark area percent (DAP) and light area percent (LAP) as retinal measurements; total choroidal area (TCA), luminal choroidal area (LCA), stromal choroidal area (SCA), luminal area percent or choroidal vascularity index (CVI) and stromal area percent (SAP) as choroidal measurements have been investigated for vertical and horizontal OCT scans. 6500 µm of the total retinal and choroidal area have been binarized and analyzed in 100 µm intervals and further divided into three main parts: inner, middle, and outer. Results: CVI value for the entire vertical scan is 69.2±2.6, whereas the entire horizontal scan is 70.1±2.7 (p=0.019). Entire inner part CVI of the vertical scans are calculated as 74.5±4.6 and in horizontal scans as 74.8±5.0 (p=0.678). Vertical CVI of the entire middle part has higher values as 67.2 ± 3.9 than the horizontal scans as 66.0±4.1 (p=0.025). This was conversely recorded at the entire outer part, which the vertical CVI value is 66.6±4.3 and horizontal CVI value is 70.3±4.7 (p<0.001). Although there was no statistically significant difference for any of the TRA comparisons for entire region of interest, entire inner, entire middle and entire outer parts between vertical and horizontal scans (p=0.386, p=0.422, p=0.309 and p=0.352 respectively), vertical TCA measurements were significantly higher than the horizontal scans (p=0.010, p=0.013, p=0.012 and p=0.008, respectively). Conclusion: CVI and other parameters and tissue distribution indexes could be a valuable tool for differentiating and evaluating the retinal and choroidal conditions in different scan regions.